Design of Virtual Map Building Using Unity 3D with MDLC Method - Aristoteles, Aristoteles; Jasmine, Amelia; Utami, Yohana Tri; Lumbanraja, Favorisen R (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Lampung University does routine activities every new academic year for students, especially for new students college in the Faculty of Engineering, Introduction to Campus Life for New Students (PKKMB), one of the main agendas of PKKMB is introducing every building and public facilities in Civil Engineering, also every building and the room in it. The current state of the COVID-19 pandemic makes the University of Lampung conduct learning activities by network (online).The area and number of buildings' public facilities will be an issue for new students and visitors since it takes longer to find information, explore, and understand the layout of the building environment. To address these issues, there is a need for technology that fulfills the requirements of information, efficiency, and new methods in introducing a building to visitors. These problems are expected to be resolved by developing a virtual 3D map application for Building A, the Dean of the Faculty of Engineering, and Building B the architectural engineering. The Multimedia Development Life Cycle (MDLC) method was used to develop this application. The application testing in this research uses two types of testing namely Alpha and Beta testing with a black box scheme. Alpha testing results show that the app is compatible with Android OS 8.1 to 11.1 and smartphones with 5.45 to 6.4-inch displays. It requires at least 4GB to 8GB RAM According to the Beta Testing the application resulted in an outstanding 90.2 percent satisfaction rate. It can be concluded that the virtual 3D map application for Dean's Office Building A and Architecture Engineering Building B of the Faculty of Engineering at Lampung University functions effectively and is rated as